Plasma Level of ADAMTS13 or IL-12 as an Indicator of HBeAg Seroconversion in Chronic Hepatitis B Patients Undergoing m-ETV Treatment - Yang, Jiezuan; Guo, Renyong; Yan, Dong; Lu, Haifeng; Zhang, Hua; Ye, Ping; Jin, Linfeng; Diao, Hongyan; Li, Lanjuan (Frontiers in Cellular and Infection Microbiology, 2020)
The ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin motif repeats 13) is a key factor involved in coagulation process and plays a vital role in the progression and prognosis of chronic hepatitis B (CHB) patients with antiviral treatment. However, there are few reports about the profile of plasma ADAMTS13 in CHB patients during entecavir maleate (m-ETV) treatment. One hundred two HBV e antigen (HBeAg)–positive CHB patients on continuous m-ETV naive for at least 96 weeks were recruited. Patients with liver cirrhosis were excluded using liver biopsies and real-time elastography. Plasma ADAMTS13 and interleukin 12 (IL-12) levels were evaluated at baseline and12, 24, 48, 72, and 96 weeks, respectively. The change of ADAMTS13 (ΔADAMTS13) and IL-12 (ΔIL-12) possesses a significant relationship in CHB patients with HBeAg seroconversion (SC) at 48-week m-ETV treatment (p < 0.001), but no significance in patients without SC. Furthermore, Cox multivariate analysis demonstrated that the change of ADAMTS13 (IL-12) is an independent predictor for HBeAg SC at week 96, and the area under the receiver operating characteristic curve for the ΔADAMTS13 (ΔIL-12) in CHB patients with 48-week m- ETV treatment is 0.8204 (0.8354) (p < 0.001, both) to predict HBeAg SC at week 96. The results suggested that higher increased ADAMTS13 and IL-12 after 48-week m-ETV treatment contributed to an enhanced probability of HBeAg SC, although the mechanism is undetermined. Quantification of ADAMTS13 (IL-12) during m-ETV treatment may help to predict long-term HBeAg SC in CHB patients.